1997
DOI: 10.1007/s004200050232
|View full text |Cite
|
Sign up to set email alerts
|

Chemical degradation of wastes of antineoplastic agents

Abstract: Sodium hypochlorite (5.25%) is an efficient reagent for the chemical degradation of the nine drugs tested thus far.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…(11,(29)(30)(31)(32)(33) A number of studies have shown the efficiency of deactivating agents, such as sodium hypochlorite, to degrade severalif not all-investigated antineoplastic agents, but mutagenicity and other health impairing risks of the degradation products have not been excluded. (31,(34)(35)(36)(37)(38) Mostly, investigated surfaces comprised stainless steel and glass as major components of biological safety cabinets (BSCs), while other surface materials have been less considered despite the evidence that contamination could be spread in the entire preparation and administration area. Although 5-FU is the most prescribed parenteral chemotherapy agent for cancer therapy in Germany and in many other countries and also the preparation numbers of GEM have been constantly increasing during recent years, literature data on decontamination strategies for both compounds are scarce.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
See 1 more Smart Citation
“…(11,(29)(30)(31)(32)(33) A number of studies have shown the efficiency of deactivating agents, such as sodium hypochlorite, to degrade severalif not all-investigated antineoplastic agents, but mutagenicity and other health impairing risks of the degradation products have not been excluded. (31,(34)(35)(36)(37)(38) Mostly, investigated surfaces comprised stainless steel and glass as major components of biological safety cabinets (BSCs), while other surface materials have been less considered despite the evidence that contamination could be spread in the entire preparation and administration area. Although 5-FU is the most prescribed parenteral chemotherapy agent for cancer therapy in Germany and in many other countries and also the preparation numbers of GEM have been constantly increasing during recent years, literature data on decontamination strategies for both compounds are scarce.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…Sodium hypochlorite, which chemically degrades antineoplastic drugs, is restricted for use at stainless steel surfaces due to its oxidizing effects and its environmental toxicity and health impairing degradation products, i.e., other chemically active metabolites with potential mutagenic risks. (35,37,38) There is also the risk of deterioration of cleaned surfaces, which requires rinsing the surfaces with water after use to avoid corrosion phenomena. (29,39) None of the cleaning agents tested led to residual contaminations markedly exceeding 10% of the original contamination of both drugs tested.…”
Section: Cleaning Proceduresmentioning
confidence: 99%
“…in secondary sewage treatment). This has led to an intensive search for methods of chemical degradation, using oxidants such as sodium hypochlorite, hydrogen peroxide, and Fenton reagent (Fe 2+ / H 2 O 2 ) [21,22], as well as so-called ''Advanced Oxidation Processes'' using reagents such as O 3 [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have tried to find a an agent capable of inactivating, degrading, and reducing contamination with cytotoxic drugs in oncology services (48)(49)(50)(51)(52)(53)(54)(55), but the issue remains. Our study only confirms that, as we found contamination even on supposedly cleaned surfaces before drug handling began.…”
Section: Cleaning Issues and Recommendationsmentioning
confidence: 99%